Teacher Intervention During Collaborative Problem Solving in Mathematics Classrooms in Mainland China - Yixuan Liu; Yiming Cao (Behavioral Sciences)
In the Programme for International Student Assessment (PISA) 2015, students from four cities/provinces in mainland China performed worse in collaborative problem solving (CPS) than in other subjects. While student collaboration has been widely implemented in Chinese classrooms for over two decades, empirical research on teachers’ roles and interventions remains quite scarce. Influenced by international educational reform in the 21st century, educators have developed and made widespread use of open-ended tasks, perceived as more suitable for CPS, during mathematics lessons. In this study, we investigate the effect of teacher intervention during pair and small group CPS using a quasi-experiment with four teachers from eight classes. We then selected typical cases and analysed their effect on task performance regarding intervention focus and means. The result showed that three of the four teachers’ interventions proved effective. The most and least effective teachers were selected for the case study. We discuss teacher intervention’s effect in emphasising social activities and diagnosing. Considering the difference in authority between teachers in Chinese/Western classrooms, we discuss intervention styles and offer suggestions for choosing and carefully implementing appropriate forms of collaborative activities.